Performance Testing of Foldable Electric Powered Wheelch - Chaulagain, Raj Kumar; Dahal, Gaurav; Nepal, Alkesh; Tiwari, Amrit; Regmi, Pramod (Journal of Innovations in Engineering Education, 2020)
This paper aims to design and test a foldable, lightweight wheelchair propelled by a pair of electric motors. Starting from literature review, the research team carried out the design and solid modeling of proposed wheelchair. Solidworks software was used to make the computer model. The wheelchair frame comprised of a chair like frame with two pairs of wheels on front and back. The defined electric wheelchair is completed with the coordination of manual and electric system. A pair of electric motor is fitted on wheels at backside which are controlled by the electronic controller powered by the battery. The folding mechanism developed on the wheelchair was aimed for ease of transport and storage. The frame material was selected to be aluminum alloy. Lithium ion battery and geared electric motors were used in the prototype and motion control was done by joystick. Locking mechanism was used for frame locking during operation. The prototype was subjected to different tests. The unfolded dimensions of wheelchair were 850mm × 620mm × 1400mm (0.738m3) and whereas the folded dimensions were 1100mm × 620mm × 520mm (0.354m3) that resulted 52.03% reduction in volume. The mass of wheelchair was measured to be 22kg. The tested data of wheelchair was found to be 10 km approximately.